The Autonomy of Urban Commons' Reproduction in Relation to the Local State: Between Material and Decision-Making Autonomy. - Bianchi, Iolanda (PARTECIPAZIONE E CONFLITTO, 2022)
In the post-Marxist debate, commons have emerged as a means to develop an autonomous path of emancipation from capitalism. However, the extent to which commons can construct this emancipation autonomously from the state is unclear. By focusing its analysis on the city-wide scale, this article examines the extent to which urban commons are materially supported by the local state, the criteria used by the local state in offering its support, and how urban commons perceive it and its claims. The research study is set in Barcelona and presents the results of 101 responses to a survey carried out with 429 urban commons. It shows that many urban commons are able to reproduce thanks to the economic and property support of the local state, that the local state often allocates resources by exercising its discretionary power, and that many urban commons tend not to recognise this support. It concludes by putting forward two main arguments: i) a distinction should be made between material and decision-making autonomy; ii) although urban commons should pursue their material and decision-making autonomy from the state, the material support they receive from the local state can become a temporary survival strategy for them.